Analysis of high risk factors and nursing intervention measures of acquired weakness in ICU (ICU获得性衰弱发生影响因素分析及护理干预措施) - XU Qian (徐倩) (Association of Integrative Nursing, 2024)
Objective To analyze the high risk factors and nursing intervention measures of acquired weakness in intensive care unit (ICU-AW). Methods The clinical data of 261 patients with critically ill admitted to the ICU of our hospital from January 2023 to December 2023 were collected retrospectively. They were divided into the ICU-AW group (115 cases) and the non-ICU-AW group (146 cases) according to whether the patients were complicated with ICU-AW. The statistically significant factors were included in multivariate Logistic regression analysis to further analyze the risk factors of ICU-AW in patients with critically ill according to the clinical data of patients. Results Among 261 patients with critically ill, 115 patients had ICU-AW, and the incidence of ICU-AW was 44. 06%. The results of multivariate Logistic regression analysis showed that high score of acute physiological and chronic health status (score of APACHE II) and level of blood lactic acid , long time of ICU stay , and time of mechanical ventilation, diagnosis of multiple organ dysfunction, continuous renal replacement therapy and application of hormone drugs were independent risk factors for ICU-AW in patients with critically ill (OR= 3. 086, 4. 297, 1. 958, 3. 180, 3. 736, 3. 658, 4. 031, P<0. 05). Conclusion The incidence of ICU-AW in ICU patients was high, and its risk factors include high score of APACHE II on admission and level of blood lactic acid, long time of ICU stay , and time of mechanical ventilation, multiple organ dysfunction, continuous renal replacement therapy, application of hormone drugs, etc. Therefore, clinical targeted intervention can be given to ICU patients to reduce the incidence of ICU-AW and improve the prognosis of patients. (目的 分析重症监护室获得性衰弱(ICU-AW)发生的高危因素, 总结护理干预措施。方法 回顾性收集261例2023年1月-2023年12月医院ICU就诊的危重症患者的临床资料, 根据患者是否并发ICU-AW可分为ICU-AW组(115例)和非ICU-AW组(146例)。根据患者临床资料将具有统计学意义的因素纳入多因素Logistic回归分析, 以进一步分析危重症患者ICU-AW发生的危险因素。结果 261例危重症患者中有115例发生ICU-AW, ICU-AW发生率为44. 06%。多因素Logistic回归分析结果显示, 入院时急性生理及慢性健康状况评分(APACHE II评分)、血乳酸水平高、ICU入住时间和机械通气时间长、诊断为多器官功能障碍、连续肾脏替代治疗、应用激素类药物均为危重症患者ICU-AW发生的独立危险因素(OR=3. 086、4. 297、1. 958、3. 180、3. 736、3. 658、4. 031, P＜0. 05)。结论 ICU患者ICU-AW发生率较高, 且其危险因素包括入院时APACHE II评分、血乳酸水平高, ICU入住时间、机械通气时间长, 多器官功能障碍、连续肾脏替代治疗、应用激素类药物等, 临床可据此予以ICU患者针对性干预以降低ICU-AW发生率, 进而改善患者预后。)